Association of Gestational Age and Severe Neonatal Morbidity with Mortality in Early Childhood. Issue 6 (24th October 2016) - Stephens, Alexandre S.; Lain, Samantha J.; Roberts, Christine L.; Bowen, Jennifer R.; Nassar, Natasha
Abstract: Background: Although infant and child mortality rates have decreased substantially worldwide over the past two decades, efforts continue in many nations to further these declines. The identification of pertinent perinatal factors that are associated with early childhood mortality would help with these efforts. We investigated the association of two crucial perinatal factors, gestational age and severe neonatal morbidity at birth, with mortality during infancy (29–364 days) and early childhood (1–5 years). Methods: The study population included all singleton livebirths, ≥32 weeks' gestation in New South Wales, Australia in 2001–11. Birth data were linked to hospitalisation morbidity data and deaths data (linked birth cohort n = 871 916), and multivariable Cox regression models were used to assess mortality. Results: The median follow‐up time per child was 4.95 years (range 0.00–5.92 years; 3 614 738 total person‐years), with 984 deaths observed. Gestational age was associated with increased mortality, and specifically from deaths attributable to infections, respiratory conditions, and injuries during infancy, but not during early childhood. Severe neonatal morbidity strongly mediated the effects of gestational age during infancy, but not during early childhood, and was associated with increased mortality from circulatory, nervous, and respiratory system causes. Conclusions: The direct effects of gestational age on mortality extended up to 1 year of age, whereas severe neonatal morbidity remained associated with heightened mortality into early childhood. Efforts to maximise the health and well‐being of vulnerable infants, with emphasis on preventing infections and injuries, may help further reduce early childhood mortality.